93.9k views
2 votes
Sketch a graph of
y=3(x − 2)(x + 1) (x – 4)

ASAPP!

1 Answer

3 votes

Answer:

Use the distributive property to multiply 3 by x−2.

y=(3x−6)(x+1)(x−4)

Use the distributive property to multiply 3x−6 by x+1 and combine like terms. y=(3x 2 −3x−6)(x−4)

Use the distributive property to multiply 3x 2 −3x−6 by x−4 and combine like terms. y =3x 3 −15x 2 +6x+24

Explanation:

I also up a link there of a graph. Please tell me if you can open it. Hope this helps! :P

Sketch a graph of y=3(x − 2)(x + 1) (x – 4) ASAPP!-example-1
User Merours
by
5.0k points